2013
DOI: 10.1016/j.jflm.2013.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Fatal cranial injury in an individual from Messina (Sicily) during the times of the Roman Empire

Abstract: a b s t r a c tForensic and archaeological examinations of human skeletons can provide us with evidence of violence. In this paper, we present the patterns of two cranial lesions found on an adult male (T173) buried in a grave in the necropolis 'Isolato 96', Messina, Sicily, dating back to the Roman Empire (1st century BC -1st century AD). The skull reveals two perimortem traumatic lesions, one produced by a sharp object on the right parietal bone and the other one on the left parietal bone, presumably the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…There are also some papers regarding carnivore activity on fossil crania (Arsuaga et al, 2007;Boaz et al, 2004;Sala et al, 2014). In archaeological contexts there are studies of fracture patterns on cranial remains (Berryman and Haun, 1996;Jordana et al, 2009;Kanz and Grossschmidt, 2006;Messina et al, 2013;Miraz on-Lahr et al, 2016;Spencer, 2012;Walker, 1989); nevertheless, there is a lack of specific research addressing fracturation analyses of hominin cranial in particular and flat bones in general in Pleistocene contexts.…”
Section: Introductionmentioning
confidence: 99%
“…There are also some papers regarding carnivore activity on fossil crania (Arsuaga et al, 2007;Boaz et al, 2004;Sala et al, 2014). In archaeological contexts there are studies of fracture patterns on cranial remains (Berryman and Haun, 1996;Jordana et al, 2009;Kanz and Grossschmidt, 2006;Messina et al, 2013;Miraz on-Lahr et al, 2016;Spencer, 2012;Walker, 1989); nevertheless, there is a lack of specific research addressing fracturation analyses of hominin cranial in particular and flat bones in general in Pleistocene contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Forensic evidence suggests that this early modern European suffered a violent death caused intentionally by another human. Signs of interpersonal violence with a variety of weapons are very common in antiquity [30,3638]. Previous work has showed a level of interpersonal aggression among Neanderthals[39,40] and even earlier hominins[4143], and early Holocene hunter-gatherers[44] (although some of this evidence has been questioned[45]).…”
Section: Discussionmentioning
confidence: 99%
“…Studies which apply digital microscopy to investigate skeletal traumas in archaeological samples remain relatively rare and the current study represents one of the few that does (Messina et al, 2013;Appleby et al, 2014;Constantinescu et al, 2015). The principal question addressed here was to assess whether digital microscopy can provide valuable information on trauma that may compensate for the limitations of macroscopic observation (Ubelaker and Adams, 1995;Nahkhaeizadeh et al, 2014).…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…Offering technical capabilities, such as three-dimensional and depth of field enhancements, the utility of such a tool is a subject of on-going refinements and discussions (Bello et al, 2009). This method has been applied to archaeological examples involving considerable numbers of purported weapon-related injuries (Jantzen et al, 2010;Messina et al, 2013;Appleby et al, 2014;Constantinescu et al, 2015), although its effectiveness remains to be confirmed.…”
Section: Introductionmentioning
confidence: 99%